The absolute value of Mike - Erskine, Kathryn (Puffin Books, 2012)
Fourteen-year-old Mike, whose father is a brilliant mathematician but who has no math aptitude himself, spends the summer in rural Pennsylvania with his elderly and eccentric relatives Moo and Poppy, helping the townspeople raise money to adopt a Romanian orphan.